The state of health in the European Union in 2019. (20th October 2021) - Vasco Santos, J; Padron Monedero, A; Bikbov, B; Grad, DA; Plass, D; Mechili, E-A; Gazzelloni, F; Fischer, F; Sulo, G; Ngwa, CH; Noguer-Zambrano, I; Peñalvo, J; et al.
Abstract: Background: The European Union (EU) faces many health-related challenges. Accurate and timely data on mortality and morbidity from diseases and injuries and their trends over time are essential for health planning and priority setting. Methods: We use the GBD 2019 study estimates and 95% uncertainty intervals for the whole EU and each country to evaluate age-standardized death, YLL, YLD and DALY rates for Level 2 causes. We evaluate trends by comparing estimates for the year 2019 with those for the year 2010. Results: In 2019, the age-standardized death and DALY rates in the EU were 465.8 and 20 251.0 per 100 000 inhabitants, respectively. Between 2010 and 2019, there were significant decreases for age-standardized, death and YLL rates across EU countries. However, YLD rates remained mainly unchanged, with increases in the Netherlands and the '. The largest decreases in age-standardized DALY rates were observed for HIV/AIDS and sexually transmitted diseases and transport injuries (both -19%). On the other hand, only diabetes and kidney diseases showed a significant increase for age-standardized DALY rates in the EU (3.5%). Mental disorders showed an increasing age-standardized YLD rate, as well. Conclusions: Overall, there was a visible trend of improvement in the health status in the EU with substantial differences between countries. EU health policy makers need to tackle incidence of diseases and injuries, with specific attention to causes such as mental disorders. There are many opportunities for mutual learning among otherwise similar countries with different patterns of disease.